Utilization of Cupping Therapy in the Treatment of Vascular Thoracic Outlet Syndrome in a Collegiate Pitcher: A Case Study - Stephen A. Cage; Diana M. Gallegos; Brandon J. Warner (Bowling Green State University, 2017)
Objective: Present a clinical case detailing the effectiveness of dry cupping therapy in treating thoracic outlet syndrome. The utilization of dry cupping therapy on a 20-year-old collegiate baseball pitcher with diagnosed thoracic outlet syndrome is presented. Background: Thoracic outlet syndrome is a relatively rare musculoskeletal condition affecting 1/100,000 patients annually. Dry cupping therapy is an ancient therapeutic modality that utilizes various means of suction with the goal of decompressing myofascial layers. Treatment: Following diagnosis, patient was successfully treated in two weeks using dry cupping therapy. The patient experienced no further incidence of thoracic outlet syndrome symptoms and was able to complete the remainder of his competitive season. Uniqueness: The patient's thoracic outlet syndrome was diagnosed at an early stage, leading to the need of clearance from a vascular specialist before returning to competition. To the author's knowledge, there are currently no published case reports detailing the use of cupping therapy to treat thoracic outlet syndrome. Conclusion: Cupping therapy may be a viable treatment option when seeking to address tight musculature. Further research needs to be conducted to determine optimal parameters for cupping therapy as a therapeutic modality.